Soil moisture monitoring using sheet-type GHz metamaterial perfect absorber - Fumiya NOTO; Soma SATO; Hiroaki ONOE; Tetsuo KAN (Mechanical Engineering Journal)
In this study, we propose a sensor probe utilizing electromagnetic metamaterial perfect absorbers to enable the evaluation of soil properties. This device consists of periodically arrayed copper split-ring resonators (SRRs), a moisture-absorbing material, and a mesh-like aluminum structure, forming a perfect absorbing metamaterial. The mesh-like aluminum placed at the bottom surface prevents interference with soil moisture absorption while blocking reflections from the soil, thereby allowing robust soil property evaluation independent of soil reflection waves. The finite element method (FEM) simulations showed that the device with a mesh-like aluminum structure absorbed approximately 83% of the incident electromagnetic waves, compared to a configuration with no material on the bottom surface. Reflection measurements demonstrated that changes in soil moisture levels could be detected in both air and on soil surfaces without being affected by reflection waves. This study enables measurements of soil surface environments by eliminating the artifacts caused by soil reflection waves, contributing to the realization of wide-area soil property monitoring, independent of soil surface conditions.